2000
DOI: 10.1097/00004694-200011000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Development After Closed Reduction of Developmental Dislocation of the Hip

Abstract: The purpose of this study was to identify predictive factors that would best indicate possible future acetabular dysplasia after closed reduction of developmental dysplasia of the hip (DDH). We studied 32 hips for a mean of 13.5 years, during which time radiographs were analyzed annually. Overall results were evaluated using the modified Severin classification. Using the combined predictive factors of center-head distance discrepancy (CHDD) and sourcil orientation in patients between 4 and 5 years of age, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 25 publications
1
59
1
4
Order By: Relevance
“…As osteoarthritis is the end result of untreated hip dysplasia, incompletely treated hip dysplasia, and the complications of treatment, it is the final common pathway and can be used as the outcome for the decision analysis. The modified Severin classification system [28][29][30] is an intermediary outcome measure that is correlated with the eventual development of arthritis. A Severin class-I hip is normal, with a center-edge angle of >20°.…”
Section: Definition Of Outcome and Outcome Utilitiesmentioning
confidence: 99%
“…As osteoarthritis is the end result of untreated hip dysplasia, incompletely treated hip dysplasia, and the complications of treatment, it is the final common pathway and can be used as the outcome for the decision analysis. The modified Severin classification system [28][29][30] is an intermediary outcome measure that is correlated with the eventual development of arthritis. A Severin class-I hip is normal, with a center-edge angle of >20°.…”
Section: Definition Of Outcome and Outcome Utilitiesmentioning
confidence: 99%
“…Residual subluxation and acetabular dysplasia represent major causes of early-onset degenerative osteoarthritis. Several reports have suggested that secondary surgery for the sequelae should be performed before 5 or 6 years of age, accompanied by radiographic evaluation [1][2][3][4]. However, it is difficult to predict the sufficiency of remodeling of the acetabulum, which is often evaluated only on plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors advocate the use of an intraoperative stability test [42] to selectively add femoral or pelvic osteotomies to their open reductions; however, this is not a fail-proof method either. The universal addition of a pelvic procedure at the time of open reduction has been advocated by Salter [31][32][33] and others [14,15] when treating children older than 18 months of age, whereas other authors suggest that the addition of a pelvic osteotomy is unnecessary in children who are younger than 5 years of age [2,21,22]. It has been suggested that the initial preoperative acetabular index may be used as a criterion to add an acetabular procedure to the primary treatment [16].…”
Section: Discussionmentioning
confidence: 99%